ANALYSIS FINANCIAL PERFORMANCE FOOD AND BEVERAGES COMPANY IN INDONESIA - Wastam Wahyu Hidayat (JEMMA (Journal of Economic, Management and Accounting), 2024)
This study aims to determine whether there is an influence of the Current Ratio, Debt to Assets Ratio, and Debt to Equity Ratio on Return on Assets. The independent variables in this study are the Current Ratio as a proxy for the Liquidity Ratio, the Debt to Assets Ratio as a proxy for the Solvency Ratio, and the Debt to Equity Ratio as a proxy for the Solvency Ratio. While the dependent variable in this study is Return On Assets as a proxy for the Profitability Ratio. The data used in this study are the financial statements of food and beverage sector companies listed on the IDX for 2012–2021. This research uses quantitative methods. The sampling technique used in this study was purposive sampling. The results showed that the partial Current Ratio has a positive and significant effect on Return On Assets, the Debt to Assets Ratio has a positive and significant effect on Return On Assets, Debt to Equity Ratio has a negative and significant effect on Return On Assets. Simultaneously Current Ratio, Debt to Assets Ratio, and Debt to Equity Ratio have a significant and significant effect on Return On Assets